Scrutinizing the paleoecological record of the Maya forest - Ford, Anabel (Frontiers in Ecology and Evolution, 2022)
Human expansion into and occupation of the New World coincided with the great transition from the Pleistocene to the Holocene epoch, yet questions remain about how we detect human presence in the paleoecological record. In the Maya area of southern Mesoamerica, archeological evidence of the human imprint is largely invisible until ∼4,000 years ago. How do environmental changes after that time correspond and relate to human impacts? Are the archeological signatures of initial settlements in the Early Preclassic detected? Later, by ∼2,000 years ago when the Maya had fully settled the landscape, how does the evidence of forest compositional changes relate to human intervention? This paper evaluates published paleoecological data in light of the rise of the Maya civilization and reflects on interpretations of how swidden agriculture and the milpa cycle impacted the environment. Evaluating the contrast between the long archeological sequence of successful Maya development and paleoecological interpretations of destructive human-induced environmental impacts requires a concordance among pollen data, archeological evidence, ethnohistoric observations, ethnological studies of traditional Maya land use, and the historical ecology of the Maya forest today.